The Breakup of Yugoslavia in the Research and Political Discourses of Russia and Serbia - E. G. Entina; D. Prorocovic (Международная аналитика, 2022)
The breakup of Yugoslavia has become one of the key events of the postbipolar world order and has occupied a special place in the discourse in both politicians of Serbia and Russia. However, interpretations of the crisis, its causes and main driving forces, as well as its use as a reference object in contemporary national and political discourse differ significantly in Serbia and Russia. One of the important subjects is that in both countries, at the level of both discourses, there is a convergence of radical versions, and in the changing structure of European international relations, the role of an external factor in the tragedy of disintegration acquires a special sound. In this article, a discourse analysis of narratives of the Yugoslav crisis in academic and political discourse in a cross-country perspective is conducted using a social constructivist approach. The study seeks to deconstruct the images of the “guilty ones” in the Yugoslav crisis and to consider the features of using peculiarities of the crisis image in contemporary political discourse. It explores how the formal discourse of academics further influenced the discourse of politicians in the Russian and Serbian cases.